Measuring sugar intake in oral health birth cohort studies: a scoping review - Sarawagi, Shilpa; Gambetta-Tessini, Karla; Alves-Costa, Silas; Cardoso, Marly Augusto; Nascimento, Gustavo G.; Peres, Karen G. (Frontiers in Nutrition, 2026)
Numerous reviews have explored the relationship between sugar intake and various health conditions, with specific recommendations for sugar intake thresholds in medical and dental research. However, heterogeneity in dietary assessment methods used to measure sugar intake has posed challenges. This scoping review aimed to identify and map the methods assessing sugar intake in oral health birth cohort studies (OHBCS). Using the Population–Concept–Context framework, the review included participants in OHBCS, dietary assessment methods measuring sugar intake associated with oral health outcomes from studies conducted worldwide. Data from PubMed, Embase, Web of Science, Scopus, and Dentistry & Oral Sciences Source were searched until June 2025, with no date and language restrictions. Articles from a previous OHBCS scoping review and its 3-year update were also included. From 2,297 screened articles, 34 studies representing 24 OHBCS across 13 countries (77% from high-income countries) met the inclusion criteria. Dietary assessment methods to assess sugar intake identified included Food Frequency Questionnaire (FFQ, n = 11), non-specific questionnaires (n = 9), food lists (n = 7), food diary (n = 7), 24-h recall (n = 5), and structured interviews (n = 1). Methods of estimating sugar intake varied, with frequency (n = 19) being the most common, followed by quantity (n = 11), number of sugar items introduced (n = 9), energy (n = 3), and the percentage of sugar consumption (n = 2). Different types of dietary sugars were assessed, including intrinsic sugars (n = 5), milk sugars (n = 14), and free sugars (n = 34). FFQs emerged as the most frequently used sugar intake assessment method, with a focus on intake frequency. This review highlights a significant lack of standardization in sugar intake assessment across studies, underscoring the need for a unified approach to guide early interventions, inform dietary recommendations, and enhance comparability in future OHBCS research.